In the pastoral image : the dialectic of Maasai identity, Volume I and II. - Galaty, J.G. (University of Chicago, 1977)
During the years of 1968-1969 I had the honor and good fortune of teaching at Olkejuado Secondary School in Maasailand--under the auspices of the Peace Corps--and witnessing the graduation of its inaugurating class. Although located in the Maasai district of Kajiado, the school's student body was composed of members speaking eighteen different languages, representing the whole of the Kenyan nation, and thus issues of 'tribal,' regional, cultural, linguistic and national identity were forever present. The problem of 'identity,' which emerged for me at that time, was not simply political. Graduate preparation was carried out at the Department of Anthropology of The University of Chicago,with the financial assistance of the Committee on African Studies and a University of Chicago Fellowship. Assistance from the Lichstern Research Fund of the Department of Anthropology was partially used in preparation of the research proposal which served as a guideline in the execution of the study. Previous research on the maasai, carried out by Fosbrooke Hollis Jacobs and Merker provided a substantial ethnographic base on which to ground my own research aims. Specific citations have been made in the present study to unique theoretical insights, ethnographic conclusions at variance with my own results, and information untouched in my own research, but simple ethnographic facts reduplicated and verified by my own study have not been cross-referenced or cited. The advice of researchers familiar with the East African, Kenyan, and Maasai areas, was helpful during the pre-field period, in particular that of Alan Jacobs, Robert LeVine, and Donald Levine. The actual research was carried out with the assistance of an NSF Doctoral Dissertation Research Grant, SOC sponsored by the University of Chicago with the assistance of David M. Schneider. An offer of affiliation as Research Associate was made by the Bureau of Educational Research of the University of Nairobi, which provided an institutional home during the period of the study, from October, through December, I wish to acknowledge the generosity of staff of the University of Nairobi in making equipment available during my stay, often beyond the call of duty. In addition, ,the staff and the remaining cast of research associates provided welcome support during the unpredictable episodes of field research. The Kenyan National Archives were consulted through the cooperation of its director, Dr. Maina Kagombe, and the professional assistance and technical advice of J. B. Gillett of the East African Herbarium was greatly appreciated. Aside from a brief visit to areas of the Samburu and Ilchamus (Njemps), the research was entirely carried out among Maa-speaking peoples of Kajiado and Narok Districts. All-told, the Maa-speaking peoples of Kenya include Masai, Samburu, Ndorobo and Njemps, while 'Masai' occupy the Masai districts of Kajiado and Narok (Kenya Population Census), which thus represents the Masai heartland. Due to problems in obtaining research clearance, Tanzanian Maasai were not in-cluded in the study. The majority of the research was carried out among the pastoral Maasai, at sites of family dwellings and ritual villages and in and some locations of Kajiado District. Shorter periods were spent with groups of specialists and alternative productive modes in both Kajiado and Narok Districts: with hunters, at Ilkirragarian near Nairragie Enkare and Entasekera and elsewhere. A relatively large number of research sites were visited, in contra-vention of the usual norms of the intensive community study. While the study required a somewhat 'extensive' approach, several sites were occupied for periods of two-three months at a time as well as periodic revisiting, allowing for accruement of the value of relatively intensive study and longer-term friendships. Especially valued as warm friends and long-term informants were Ole Mututua and Ole Kureko, of , Ole Munga and Ole Naudo, of , Ole Koiyaki, o